Macrophage Activation Markers, Soluble CD163 and Mannose Receptor, in Liver Fibrosis - Gantzel, Rasmus Hvidbjerg; Kjær, Mikkel Breinholt; Laursen, Tea Lund; Kazankov, Konstantin; George, Jacob; Møller, Holger Jon; Grønbæk, Henning (Frontiers in Medicine, 2021)
Macrophages are essential components of the human host immune system, which upon activation facilitates a broad pallet of immunomodulatory events including release of pro- or anti-inflammatory cytokines and chemokines, restoration of immune homeostasis and/or wound healing. Moreover, some macrophage phenotypes are crucially involved in fibrogenesis through stimulation of myofibroblasts, while others promote fibrolysis. During the last decades, the role of resident liver macrophages viz. Kupffer cells and recruited monocytes/macrophages in acute and chronic liver diseases has gained interest and been extensively investigated. Specifically, the scavenger receptors CD163 and mannose receptor (CD206), expressed by macrophages, are of utmost interest since activation by various stimuli induce their shedding to the circulation. Thus, quantifying concentrations of these soluble biomarkers may be of promising clinical relevance in estimating the severity of inflammation and fibrosis and to predict outcomes such as survival. Here, we review the existing literature on soluble CD163 and soluble mannose receptor in liver diseases with a particular focus on their relationship to hepatic fibrosis in metabolic associated fatty liver disease, as well as in chronic hepatitis B and C.